Professionals' beliefs in patient involvement for hospital safety - Cristiane Chagas Teixeira; Ana Lúcia Queiroz Bezerra; Thatianny Tanferri de Brito Paranaguá; Thaisa Cristina Afonso (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the beliefs of health care professionals about the benefits of patient involvement in care during hospitalization. Methods: a descriptive, exploratory, qualitative study was conducted with 87 health professionals from a teaching hospital. Semi-structured interviews were conducted between December 2019 and January 2020 - data was submitted to content analysis and interpreted in light of Rosenstock's Model of Beliefs in Health. Results: participants included nursing technicians, nurses, doctors, and other professionals. The categories "Professionals' beliefs about patient involvement in care", "Practices of patient involvement in care" and "Factors favoring patient involvement in hospital care" emerged. The perception of professionals revealed the influence of patient involvement in care outcomes and benefits for the safety of care. Final Considerations: involving the patient in care is associated with the healthcare professional's belief in the benefits of this practice for reducing incidents.